On new method of processing of sportsmen and sports projectiles movements - Rudakov, R. N. (Russian Journal of Biomechanics, 2004)
In previous papers [1], [2] we showed how to determine aerodynamic coefficients of a volleyball and a ski-jumper by means of the video technology. Dependences of coordinates on time are obtained according to video records. Velocities and accelerations are found by coordinates numerical differentiation, and aerodynamic coefficients - by movement equations. The applied method of defining the velocities and accelerations led to a low accuracy of the found values, it is evidenced by the large scatter of aerodynamic coefficients in those studies. The currently suggested method of processing the video records is based on solving the boundary value problems of sports movements. It allows to keep the accuracy which took place in experiments. Usage of this method is illustrated by an example of a three-dimensional movement of a ball. Also it is shown that its aerodynamic coefficients may be defined without coordinates differentiation but by solving the boundary value problem with regular differentiated equations. This raises significantly the accuracy of the treatment of the videotape recording the sports motions as compared with applied methods of the aerodynamic coefficients determining.